Factors Predicting Abnormal Postoperative Neurological Symptoms in The First 24 Hours Following Craniotomy in Patients with Primary Brain Tumor - Pinchanchaiyuth, Thanatip; Chayaput, Prangtip; Chanruangvanich, Wallada; Sittinamsuwan, Bunpot (Journal of The Royal Thai Army Nurses, 2023)
This descriptive research aimed to determine predictors of abnormal neurological symptoms after the first 24 hours period of craniotomy among 385 primary brain tumor patients admitted to a single super tertiary hospital. Roy adaptation model was applied as a conceptual framework. The instruments used for data collection were demographic and clinical data record form, and abnormal neurological symptoms record form (sensitivity 0.722 and specificity 0.737). Chi–Square test and Relative Risk were employed for statistical analysis. The study results noted that most of samples were females (71.2%), had a Meningioma (57.9%), and reported an incident of abnormal postoperative neurological symptoms during the first 24 hours after surgery (49.4%). The top-three abnormal neurological symptoms, most found, included cranial nerve function deficit (26.1%), motor deficit (22.6%), and postoperative seizure (10.6%), respectively. As for statistical analysis, the results showed that tumor size greater than or equal to 4 centimeters (RR=6.94; 95%CI 4.90-9.83, p<.001) and low levels of antiepileptic drugs (RR = 1.33; 95%CI 1.02–1.74, p<.05) could predict abnormal postoperative neurological symptoms significantly.